(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To investigate the effect of Anthracyclines on left ventricular function on breast cancer patients at Thong Nhat Hospital. Objects and methods: A prospective descriptive study on 43 patients with breast cancer treated with Anthracyclines with 4 to 6 cycles as determined by the clinical doctor at Thong Nhat Hospital. Results: Percentage of left ventricular ejection, total deformation of the vertical systolic stage decreased significantly after treatment: EF before and after treatment were 60.23 ± 3.46 and 59.44 ± 3,67 (%), respectively; GLS before and after treatment were -20.01 ± 1.62 and -19.14 ± 1.82 (%), respectively. The incidence of cardiotoxicity was 6.98%. The proportion of patients with subclinical left ventricular dysfunction was 23.26%. After treatment, the proportion of respectively. The proportion of patients with subclinical systolic dysfunction was higher in the decreased diastolic function group compared to the group with normal diastolic function. Patients with normal diastolic function after treatment decreased, the proportion of patients with diastolic dysfunction increased significantly, accounting for 41.86% and 58.14% No association was found between the type of anthracycline used, also disease stage and the effect of anthracycline on left ventricular function. Conclusion: Left ventricular ejection fraction, total deformation of the vertical systolic stage reduced. The prevalence of cardiac toxicity and subclinical left ventricular dysfunction were moderate. After treatment, the proportion of patients with normal diastolic function decreased, the diastolic dysfunction increased. There was no relationship between the type of Anthracycline used, also the disease stage and the effect of Anthracycline on left ventricular function.